The impact of social media on luxury consumption - Çelik, Merve (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2016)
The main purpose of this search, to examine the effects of social media on luxury consumption. Online survey form created for the purpose, between the dates of 1-6 June 2016 social media has been applied to the 208 user. The Program SPSS 22.0 statistics of the survey data is realized through the evaluation of the achieved. Impact of social media on luxury consumption in determining the level of the participants, the average and standard deviation statistics were used, descriptive characteristics of the participants to examine the effects of social media on luxury consumption in terms of the kruskal-Wallis H and Mann-Whitney u tests were used. As a result of the research, the impact of social media on a low level of participants, the effects of luxury consumption on social media sites increased with the increment of income level and it was concluded that used. The effects of social media on luxury consumption, individuals ' gender, age, educational status, and the social media sites they use most in the research that does not vary according to other results that can be reached.
Keywords: Social Media; Social Networks; Luxury; Luxury Consumption